Benefits from Vergence Rehabilitation: Evidence for Improvement of Reading Saccades and Fixations - Daniel, François; Morize, Aurélien; Brémond-Gignac, Dominique; Kapoula, Zoï (Frontiers in Integrative Neuroscience, 2016)
We hypothesize that binocular coordination of saccades is based on continuous neuroplasticity involving interactions of saccades and vergence. To test this hypothesis we study reading saccades in young students who were diagnosed for vergence disorders before and after vergence rehabilitation. Following orthoptic evaluation and symptomatology screening, 5 weekly sessions of vergence rehabilitation were applied with the REMOBI vergence double step protocole (see Kapoula et al., 2016). Using the Eyeseecam videoculography device we measured vergence as well as saccades and fixations during a reading test four times: at the beginning and at the end of the first and of the fifth vergence rehabilitation session. The results show elimination of symptoms, improvement of clinical orthoptic scores, and importantly increase of measured vergence gain and reduction of inter-trial variability. Improvement of the vergence was associated to a decrease of the disconjugacy of saccades during reading but also to shortening of fixation durations, to reduction of the number of regressive saccades and to a better correction of the intra-saccadic disconjugacy during the following fixation. The results corroborate the hypothesis of neuroplasticity based on saccade vergence interaction in young adults. It validates the clinical validity of the vergence double-step REMOBI method as a means to improve both, vergence and reading performances. It opens a new research approach on the link between fine binocular coordination of saccades, quality of the vergence response, attention, cognition and reading.